The Volume of Production of Basic Materials in the United States, 1909-21 - Day, Edmund E. (The Review of Economics and Statistics, 1922)
T HAT violent fluctuations of production have marked the past two or three years is generally recognized. But just how great these fluctuations have been is not commonly known. Yet accurate information on this point is of distinct importance, for these have been years of radical change in the price level and extraordinary realignment in demand and supply. Accurate measurement of changes in the volume of production since I9I9 should contribute much to an understanding of the factors underlying current business conditions. Such measurement of output is afforded by the several indices which follow. The basic materials of modern commercial life have their origin in four divisions of economic activity: agriculture, animal husbandry, forestry, and mining.' The conditions of production in these four divisions are so dissimilar as to suggest a separate index for each. The separate indices may then be combined to form an index of the production of all basic materials. For a number of reasons, I9I9 is the best recent year with which to make comparison. This is true despite the fact that mineral production in I9g9 was low a fact to be taken into account in interpreting the most recent data of mine output. In most other lines I9I9 production was reasonably normal. Certainly no other year since the war serves as well as a base from which to measure subsequent fluctuations. Suppose, then, that I919 production in each major division of economic activity is taken as ioo. On this basis, production in I920 and I92I assumed the proportions shown in the following table: